(untitled) (Medico Legal Update, 2020)
The prototype E .coli - P. aeruginosa heat killed bacterin balanced and unbalanced bacterin combinations,as well as monotypic E. coli and single P. aeruginosa bacterins were developed. They were prime-boosted rabbits by homologous prime-boost protocols. At the end of the specific immune-priming protocols ,rabbits were bleed, sera saved in 0.5 ml aliquots at -18C till testing due time.IL17 Eliza assay was done on the test and control sera. Single strength balanced combined bacterin combination induced increase in the mean IL17 concentration means as compared to monotypic, double balanced ,un-balanced bcterin combinations and control. The other combinations were showing inhibition in IL17 concentration means than control .The immune interference matched To as: one bacterin enhance the other, and one damp the other. Enhancement of IL17 response single strength combination might be a promise for efficacy of such combination in regulation and protection against natural or experimental infectious challenges .